From past to better public health programme planning for possible future global threats: case studies applied to infection control - Roberte Manigat; France Wallet; Jean-Claude André (Istituto Superiore di Sanità, 2010)
The impact of weather change and global pollution on the development and/or the transformation of microorganisms is no longer to be demonstrated. In this respect, heavy trends can be taken into account. This general context needs the development of anticipation procedures and the knowledge of the perception of prevention by the public for short, medium and long term actions. After a short discussion on the concept of emerging issues, the authors present some past examples of public health programs. These examples (malaria, dengue, chikungunya and cholera) are used to propose optimized ways of decision/action that may help to avoid possible crisis in a rapidly changing world. Then, the different lessons learnt are, under certain limits, associated with a forecasting analysis.